De-novo Assembly of Limnospira fusiformis Using Ultra-Long Reads - Hicks, McKenna; Tran-Dao, Thuy-Khanh; Mulroney, Logan; Bernick, David L. (Frontiers in Microbiology, 2021)
The Limnospira genus is a recently established clade that is economically important due to its worldwide use in biotechnology and agriculture. This genus includes organisms that were reclassified from Arthrospira, which are commercially marketed as “Spirulina”. Limnospira are photoautotrophic organisms that are widely used for research in nutrition, medicine, bioremediation, and biomanufacturing. Despite its widespread use, there is no closed genome for the Limnospira genus, and no reference genome for the type strain, Limnospira fusiformis. In this work, the L. fusiformis genome was sequenced using Oxford Nanopore Technologies MinION and assembled using only ultra-long reads (>35 kb). This assembly was polished with Illumina MiSeq reads sourced from an axenic L. fusiformis culture; axenicity was verified via microscopy and rDNA analysis. Ultra-long read sequencing resulted in a 6.42 Mbp closed genome assembled as a single contig with no plasmid. Phylogenetic analysis placed L. fusiformis in the Limnospira clade; some Arthrospira were also placed in this clade, suggesting a misclassification of these strains. This work provides a fully closed and accurate reference genome for the economically important type strain, L. fusiformis. We also present a rapid axenicity method to isolate L. fusiformis. These contributions enable future biotechnological development of L. fusiformis by way of genetic engineering.